Elements of the teacher development system in learning management according to the concept of Education 4.0 - Jedsada Janpleng; Karn Ruangmontri (Journal of Green Learning, 2021)
The purpose of this study was to study the elements of the teacher development system in learning management according to the concept of Education 4.0 with a professional learning community process in secondary schools under the Office of the Basic Education Commission by studying the components of the teacher development system in learning management according to the concept of education 4.0 with a professional learning community process from 7 experts, consisting of 1) two people in higher education administration, 2) one person who has a stake in learning management, 3) two school directors, and 4) two teaching specialist teachers. The sample group was obtained by using a specific selection method using the teacher development system component assessment in learning management according to the concept of education 4.0 with a professional learning community process in secondary schools, under the Office of the Basic Education Commission, which is a 5-level rating scale. System Components Teacher development in learning management According to the educational model 4.0 with a professional learning community process in secondary schools, under the Office of the Basic Education Commission, there are 4 main components, 13 subcomponents, namely; 1) The inputs consist of (1) executives, (2) learning management courses, (3) teachers, (4) resources that support learning management. 2) The process consists of (1) Identifying challenging problems, (2) Concept finding stage, (3) Planning and development stage, (4) Testing and evaluation stage, (5) Presenting results to society. 3) Productivity consists of (1) Teachers have knowledge and understanding of learning management, (2) Teachers are competent in learning management. 4) feedback, which consists of (1) reporting on results and (2) improvements, corrections, and developments. And, the experts assess the suitability of the elements at a high and highest level and have consistent opinions on all components..